Understanding Clinician Knowledge About Race Adjustment in the Vaginal Birth After Cesarean Calculator - Julia Cron; Amelia A. Shapiro; Laura Carasimu; Julia Iyasere; Johanna M. Schisler; Szilvia Nagy; Sandra Angus; Anna Burgansky; Ashlesha K. Dayal; Tracy Bohn Hemmerdinger; Denise Howard; Corrina Oxford-Horrey; et al. (Health Equity)
Disparities in maternal health outcomes are striking. Historical and biased clinical support tools have potential to exacerbate inequities. In 2022, NewYork-Presbyterian, with ∼25,000 annual births, and our academic partners, Columbia and Weill Cornell, launched a program to better understand practice patterns and clinician attitudes toward a vaginal birth after cesarean (VBAC) calculator, which predicts VBAC success. This article summarizes the program, focusing on the VBAC calculator utilization survey, which measured provider awareness of the revised calculator and key factors considered in patient counseling. Our preliminary findings warrant future research and education on the calculator's implications for counseling and outcomes.